A heuristic model for MRI turbulent stresses in Hall MHD. Issue 1 (28th April 2016) - Lingam, Manasvi; Bhattacharjee, Amitava
Abstract: Although the Shakura–Sunyaev α viscosity prescription has been highly successful in characterizing myriad astrophysical environments, it has proven to be partly inadequate in modelling turbulent stresses driven by the magnetorotational instability (MRI). Hence, we adopt the approach employed by Ogilvie, but in the context of Hall magnetohydrodynamics (MHD), to study MRI turbulence. We utilize the exact evolution equations for the stresses, and the non-linear terms are closed through the invocation of dimensional analysis and physical considerations. We demonstrate that the inclusion of the Hall term leads to non-trivial results, including the modification of the Reynolds and Maxwell stresses, as well as the (asymptotic) non-equipartition between the kinetic and magnetic energies; the latter issue is also addressed via the analysis of non-linear waves. The asymptotic ratio of the kinetic to magnetic energies is shown to be independent of the choice of initial conditions, but it is governed by the Hall parameter . We contrast our model with an altered version of the Kazantsev prescription from small-scale dynamo theory, and the Hall term does not generally contribute in the latter approach, illustrating the limitations of this formalism. We indicate potential astrophysical applications of our model, including the solar wind where a lack of equipartition has been observed.